Occupational therapy with older people into the 21st century - Mountain, Gail Anne (Emerald Publishing Limited, 2023)
There has been significant societal and global change in recent years with accompanying shifts in how older people are perceived by societies across the world. Different treatment and care possibilities are emerging but concerns about the implications of our longevity also continue to be raised. The value of occupational therapy is greater than ever before, given its work across health and social care boundaries. Occupational Therapy with Older People Into the 21st Century demonstrates the ways in which occupational therapists can maximise this potential to the benefit of older people. Using best evidence as well as professional and personal perspectives, Mountain explores the realities of later life, ageing in place, the implication of the technological age, meeting needs for rehabilitation, revisiting and valuing the core principles of occupational therapy, and more. In contrast to other works in this space, Occupational Therapy with Older People Into the 21st Century appraises the totality of interdisciplinary evidence in light of policy and global and national trends, highlighting how evidence generated by other disciplines as well as that created by occupational therapists can be harnessed by the profession.
Includes index.
Keywords: Occupational therapy for older people.; Medical -- Allied Health Services / Occupational Therapy.; Care of the elderly.; elektronické knihy; electronic books